Multidimensional programming - Ashcroft, Edward A. (Oxford University Press, 1995)
This book describes a powerful language for multidimensional declarative programming called Lucid.Lucid has evolved considerably in the past ten years.The main catalyst for this metamorphosis was the discovery that Lucid is based on intensional logic, one commonly used in studying natural languages.